2017
DOI: 10.1111/jopr.12680
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Resilient Liner after Brushing with Conventional and Experimental Ricinus communis‐Based Dentifrices

Abstract: The use of experimental dentifrice could be indicated, as it showed similar results to the specific dentifrice, keeping the resilient material properties within acceptable values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
0
19
0
4
Order By: Relevance
“…Leite et al (8) evaluated experimental dentifrices based on Ricinus communis with different concentrations (1, 2, 5 and 10%) by the test-well diffusion in agar against microorganisms and found good results with 10%, which concentration, as part of the composition of the dentifrice, that was efficient against bacteria and fungus. In another study, the experimental dentifrice based on Ricinus communis at 10% showed similar results to the specific dentifrice for dentures, keeping the resilient material properties (abrasiveness, hardness and color stability) within acceptable values (9). The results of studies with the use of this plant are promising (5)(6)(7)(8)(9)(10) and require laboratory and clinical researches.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Leite et al (8) evaluated experimental dentifrices based on Ricinus communis with different concentrations (1, 2, 5 and 10%) by the test-well diffusion in agar against microorganisms and found good results with 10%, which concentration, as part of the composition of the dentifrice, that was efficient against bacteria and fungus. In another study, the experimental dentifrice based on Ricinus communis at 10% showed similar results to the specific dentifrice for dentures, keeping the resilient material properties (abrasiveness, hardness and color stability) within acceptable values (9). The results of studies with the use of this plant are promising (5)(6)(7)(8)(9)(10) and require laboratory and clinical researches.…”
Section: Introductionmentioning
confidence: 83%
“…In another study, the experimental dentifrice based on Ricinus communis at 10% showed similar results to the specific dentifrice for dentures, keeping the resilient material properties (abrasiveness, hardness and color stability) within acceptable values (9). The results of studies with the use of this plant are promising (5)(6)(7)(8)(9)(10) and require laboratory and clinical researches.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For complete dentures, castor oil ( Ricinus communis ) has been evaluated as a cleanser due to its antifungal and antibacterial characteristics, confirmed by studies related to endodontics . According to Pisani et al, R. communis can be seen as an alternative, inexpensive, and safe substance to be used by the population.…”
mentioning
confidence: 99%